Supervisory feedback in the principal evaluation process - Ahmed Mohammed Alkaabi; Suhair Ali Almaamari (Institute of Advanced Engineering and Science, 2020)
The purpose of this qualitative study is to understand how school principals perceive their supervisors’ feedback in the formative principal evaluation process. It spotlights the benefits of supervisors giving effective feedback to school principals as a key component in formative evaluations. In addition, it uses a qualitative case study design situated within the context of the Al-Ain school district, which is supervised by the Abu Dhabi Education Council in the United Arab Emirates. The data was collected using several data collection methods, namely interviews, documents, and field notes. Six school principals participated in the study, and a thematic analysis of their comments and other information that they provided yielded four themes that reflected the quality of feedback they received: (1) feedback in absentia, (2) superficial or irrelevant feedback, (3) negative or judgmental feedback, and (4) constructive and individualized feedback. The evidence concludes that feedback aimed at improving the leadership practices of principals is limited, and there is no embedded professional learning dialogue wherein such feedback exists. This study adds to the body of leadership literature and sets forth implications for enhancing and redesigning feedback delivery in the formative evaluation process to improve principals’ practices and support their professional growth.